Marketing Strategies at Retail Be Smart in Increasing Sales - Trianti, Khoiriyah; Zaini, Muhammad Rizki; Yasmin Nurul Zakkiya (Universitas Islam Malang, 2024)
For a Be Smart Retail, a suitable marketing concept is a social marketing concept because current market conditions are a buyer's market, so customers are everything. Customer needs, desires and satisfaction must really be considered. Objective it was founded Sunday mart This is look for profit, The same with companies other Which Also look for profit. This research uses qualitative methods. Qualitative methods are research procedures that produce descriptive data: speech or writing and observable behavior of the people (subjects) themselves. It was concluded that Retail Be Smart has succeeded in implementing various effective marketing strategies to increase sales volume. It was concluded that Retail Be Smart has succeeded in implementing various effective marketing strategies to increase sales volume. By understanding the concept of market segmentation, determining the right target market, and determining a unique market position, Be Smart is able to attract consumer attention and maintain its advantage in the market. In addition, by using the right marketing mix, SWOT Analysis also helps a company to understand its internal strengths, identify external opportunities and threats.